VD_FINDINFO HC / 2014 / 602 vom 5. August 2014 - VD Tribunal cantonal (2014)
EXPULSION DE LOCATAIRE, EXÉCUTION FORCÉE, SUSPENSION DU DÉLAI, REJET DE LA DEMANDE | 257d al. 1 CO, 257d CO, 341 al. 1 CPC (CH), 341 CPC (CH)